Papel do setor financeiro bancário na economia do Estado do Ceará - Mota, João Ademar Bastos da Silva (2021)
The objective of this dissertation is to verify the relative importance of the sector of financial activities, insurance and related services in the Ceará economy through an instrumental Matrix Insumo-Product. It is understood that the number of authors who support the existence and relevance of direct impacts of financial development on the growth of the economy ends up being greater, in addition to much of this relationship being supported by ample empirical evidence. Thus, the main objective would be to verify the relative importance of the sector of financial activities, insurance and related services in the economy of Ceará through an instrumental Matrix Input-Product. In this way, one could also investigate the impact on the Gross Domestic Product (GDP) of the State of Ceará in the absence of the sector of financial activities, insurance and related services in the Banking System.